Development and validation of two questionnaires: Dental home care and dental health in Swedish dogs - Brunius Enlund, Karolina; Brunius, Carl; Hanson, Jeanette; Hagman, Ragnvi; Höglund, Odd Viking; Gustås, Pia; Pettersson, Ann (PloS one, 2019)
Dental disease is one of the most common health problems in dogs. However, no studies have investigated the attitudes, opinions and practices of dog owners, veterinarians and veterinary nurses regarding dental health and preventative dental home care in dogs. The objective of this study was therefore to develop and validate questionnaires for this purpose, in accordance with survey methodology guidelines. Questionnaire items were determined based on the authors' academic knowledge and clinical experience, and modified throughout the validation process. Several measures were taken to reduce sampling, coverage, measurement and non-response errors. Content validity was assessed by Subject-Matter Experts (SME) and cognitive interviews were conducted in accordance with the "think-aloud protocol". Non-response analysis was performed using several methods. Constructs were identified using exploratory factor analysis and two predefined constructs from the dog owner questionnaire were confirmed "Dog owners' attitudes towards brushing their dog's teeth" (Cronbach's α = 0.86) and "Dog owners' assessment of their dog's dental health" (α = 0.76). Additionally, exploratory factor analysis identified three potential constructs. In the veterinary health practitioner questionnaire, two constructs were identified: "Veterinary health practitioners' attitudes towards dental chews and dental feed" (α = 0.78) and "Veterinary health practitioners' attitudes and opinions on dental problems and dental cleaning" (α = 0.73). Non-response analysis showed a higher proportion of women in the sample of dog owners and veterinarians compared to the target populations. Veterinarians in the sample were also younger. In contrast, gender and age distributions in veterinary nurses did not differ between sample and target. The validation presented in this work showed that the developed questionnaires could be used as accurate and reliable tools for measuring attitudes and practices regarding dental home care in dogs among Swedish dog owners, veterinarians and veterinary nurses.